Peningkatan Pemahaman Siswa pada Aspek Qiroah Melalui Metode Jigsaw di Kelas IX C MTs Negeri Semarang Tahun Pelajaran 2019/2020 - Aan Muanah (The Arabic Education Department Postgraduate Programs, UIN Sultan Maulana Hasanuddin Banten in Partnership with PPJKBA Indonesia, 2021)
This study aims to determine the efforts to increase students' understanding of the qiroah aspect through the jigsaw method. The research method used classroom action research, this research was conducted at MTs Negeri Semarang Class IX C with 35 students. The design of this research is planning, implementation/action, observation and reflection. From the results of the study, it can be concluded that in the first cycle students still look confused with their assignments in class. The results of the understanding of the first cycle obtained a score of 131, meaning that students' understanding of the Qiroah aspect was good, and the number of students who had completed learning was 28 students, while the average class of the first cycle was 75,79. While in cycle II it was stated that students' interest in learning material increased. The results of the understanding of the second cycle obtained a score of 174 which means that the students' understanding of the Qiroah aspect is very good, and the number of students who have completed learning is 35 while the average class of the second cycle is 80,48.